Non-Coronary Aortic Sinus Dilatation with Aortic Regurgitation in a Marfans Syndrome Patient - A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Aneurysm of the coronary sinus is an uncommon clinical condition. It is rare to come across an uncomplicated aneurysm as it remains silent and most of the available literature describe treatment plan after a rupture has taken place. Our case a 41 year old female also had aortic regurgitation and was a Marfan Syndrome patient. We carried out a modified Bentall's procedure on an elective basis for this patient. It may be noted this is the first time such a surgical procedure has been carried out successfully in Bangladesh. Here we describe the rationale in deciding our treatment plan. DOI: 10.3329/jbcps.v28i3.6513J Bangladesh Coll Phys Surg 2010; 28: 183-188